How Liquid are Liquid Hedge Funds? - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2009)
Many hedge funds impose minimal share restrictions and allow investors to redeem on a monthly basis or better. We find that there is significant variation in the liquidity risk exposure of these “liquid” funds. Within this group of funds, those that embrace liquidity risk outperform those that eschew liquidity risk by 4.86 percent per year. As a consequence of the liquidity risk exposure, funds experiencing outflows subsequently earn lower returns than funds receiving inflows. The effects of flows are more pronounced for funds employing leverage, for funds with high liquidity risk exposure, and during a liquidity crunch. These results underscore the importance of funding liquidity (the ease with which traders can obtain capital) and shed light on the asset-liability mismatch in the hedge fund industry.